2008
DOI: 10.1590/s0102-311x2008001200026
|View full text |Cite
|
Sign up to set email alerts
|

Visceral leishmaniasis in large Brazilian cities: challenges for control

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
34
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 26 publications
3
34
0
4
Order By: Relevance
“…The peri-urbanization of visceral leishmaniasis in Belo Horizonte, presented by Oliveira et al 6 as an example of this process in Brazil, was similar to that observed in the Northeast, with subsequent spread to other cities in the Southeast and Central-West. It is worrisome that these endemic areas have a high population density, thus placing the population at increased risk of infection.…”
supporting
confidence: 74%
See 1 more Smart Citation
“…The peri-urbanization of visceral leishmaniasis in Belo Horizonte, presented by Oliveira et al 6 as an example of this process in Brazil, was similar to that observed in the Northeast, with subsequent spread to other cities in the Southeast and Central-West. It is worrisome that these endemic areas have a high population density, thus placing the population at increased risk of infection.…”
supporting
confidence: 74%
“…The articles in this Forum 5,6,7,8 discuss key aspects related to the urbanization of visceral leishmaniasis in Brazil, including new approaches to deal with the disease and conditioning factors for the vector's capacity to transmit Leishmania. The complexity of vector and reservoir control is identified as a factor that hinders the management of visceral leishmaniasis in the country.…”
mentioning
confidence: 99%
“…Prevalence rates can vary due to the diagnostic test used and the way dogs were recruited for the study 25 The geographic expansion of CVL has been recorded in other states of Brazil, attributed to various factors such as difficulties in eliminating reservoirs, epidemiological diversity of the affected regions, high financial costs of sustaining control measures, the vector's high capacity to adapt to the peridomicile, and insufficient control measures 26 .…”
Section: Discussionmentioning
confidence: 99%
“…The importance of environmental transformations in the process of urbanization of VL in Brazil has been highlighted by various authors 3,4,27,28 , but there are still few studies specifically designed to evaluate the role of land use and land cover characteristics in the occurrence of VL in the urban environment, and especially studies focusing on the canine population.…”
Section: Discussionmentioning
confidence: 99%